EFEKTIFITAS SISTEM PEMBELAJARAN CYBER BERBASIS APLIKASI GOOGLE MEET UNTUK MAHASISWA PGMI - Mubaidilla, Irfa'i Alfian; Ainiyah, Ziana Dhurrotul; Hidayah, Alfinatul (PREMIERE : Journal of Islamic Elementary Education, 2022)
In the current era, lecturers can provide information without having to meet students directly. The most modern situation is the growth of so-called "virtual teaching," or teaching methods carried out with the help of the Internet. Another term that is gaining popularity today is "e-learning," a learning model that utilizes the power of information and communication technology, especially the internet. The use of digital media in the learning process, apart from making it easier for students, can also chat comments with the menu that has been provided, so that students who lack confidence when in a crowd can be active with the menu. The most important aspect of the learning process, whether online or offline, is the learning process itself. This study used a qualitative research method, and the data were described descriptively. This research was conducted in 2022 during the midterm for 7th semester PGMI students at IAINU Tuban, with the aim of knowing the effectiveness of using online applications in the learning process. Data collection techniques are carried out by analyzing student learning motivation, student participation, and student activity during the lecture process using online applications. The learning process using the Google Meet application as an alternative learning medium has a positive impact on students. Where it shows the spirit of student motivation rising, student participation in attending lectures reaches 100%, and student activity also seems to reach 80%.